Representasi Sejarah Tjong A Fie Melalui Koleksi Museum Tjong A Fie Mansion - Annisa Annida Nasution; Siti Fatimah (Jurusan Sejarah FIS UNP, 2026)
Museums, as a medium of public history, play an important role in shaping public understanding of historical figures through the collections, spatial arrangements, and narratives presented to visitors. However, historical representations displayed in museums are not always neutral, as they result from the selection and interpretation of particular aspects of the past. Although Tjong A Fie has been widely studied from economic, philanthropic, and architectural perspectives, studies examining the historical representation of Tjong A Fie through museum collections from a public history perspective remain limited. This study aims to analyze the historical representation of Tjong A Fie constructed through the collections displayed at the Tjong A Fie Mansion Museum. The research employs the historical method, consisting of heuristics, source criticism, interpretation, and historiography. Data were collected through observation, interviews, documentation, and literature review. The findings show that the representation of Tjong A Fie is constructed through collections displayed within public, private, domestic, and symbolic-religious spaces. Through these collections and spatial arrangements, the museum represents Tjong A Fie as a successful entrepreneur, a leader of the Chinese community, a philanthropist, and a figure who maintained close relationships with various social groups in colonial Medan. The study concludes that the museum functions not only as a repository of historical collections but also as a public history medium that shapes public understanding of Tjong A Fie's life and contributions to the history of Medan.